A rule-based, dose-finding design for use in stroke rehabilitation research: methodological development. Issue 4 (December 2017) - Colucci, E.; Clark, A.; Lang, C.E.; Pomeroy, V.M.
Abstract: Background: Dose-optimisation studies as precursors to clinical trials are rare in stroke rehabilitation. Objective: To develop a rule-based, dose-finding design for stroke rehabilitation research. Design: 3 + 3 rule-based, dose-finding study. Dose escalation/de-escalation was undertaken according to preset rules and a mathematical sequence (modified Fibonacci sequence). The target starting daily dose was 50 repetitions for the first cohort. Adherence was recorded by an electronic counter. At the end of the 2-week training period, the adherence record indicated dose tolerability (adherence to target dose) and the outcome measure indicated dose benefit (10% increase in motor function). The preset increment/decrease and checking rules were then applied to set the dose for the subsequent cohort. The process was repeated until preset stopping rules were met. Participants: Participants had a mean age of 68 (range 48 to 81) years, and were a mean of 70 (range 9 to 289) months post stroke with moderate upper limb paresis. Model task: A custom-built model of exercise-based training to enhance ability to open the paretic hand. Outcome measure: Repetitions per minute of extension/flexion of paretic digits against resistance. Analysis: Usability of the preset rules and whether the maximally tolerated dose was identifiable. Results: Five cohorts of three participants were involved. Discernibly different doses were set for each subsequent cohort (i.e. 50, 100, 167, 251 and 209 repetitions/day). The maximally tolerated dose for the model training task was 209 repetitions/day. Conclusions: This dose-finding design is a feasible method for use in stroke rehabilitation research.